PENGARUH GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA LINGKUNGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2023 - Arizal Cahyo Anasti,; Linda Grace Loupatty, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
This study aims to examine the effect of Green Acccounting and Corporate Social Responsibility (CSR) on financial performance and Corporate Social Responsibility (CSR) on Environmental Performance in Mining Companies listed on the Indonesia Stock Exchange (IDX). on Mining Companies listed on the Indonesia Stock Exchange (IDX) in 2023. This research is quantitative research. Data in study this research is secondary data obtained from the Indonesia Stock Exchange website, namely www.idx.co.id. The population in this study are 86 mining companies in the energy sector and basic materials listed on the Indonesia Stock Exchange (BEI) in 2023. The sample in this study are 30 companies that have met the criteria. Data analysis method in this study uses multiple linear regression analysis. The results of this study indicate that Green Accounting have no effect on Environmental Performance and Corporate Social Responsibility (CSR) have no effect on environmental performance in Mining Companies. Companies listed on the Indonesia Stock Exchange (BEI) in 2023.